Protected versus unprotected area with reference to fishes, corals, macro invertebrates, and CPUE in Honda Bay, Palawan - Gonzales, Benjamin J.; Becira, Joel G.; Galon, Wendell M.; Gonzales, Maria Mojena G. (2014)
The impact of Sabang Reef Fish Sanctuary in Honda Bay, Palawan was evaluated using fish, coral cover, macro-invertebrates and CPUE as measures for success. Visual census and LIT methods were used for fish, macro-invertebrate and coral cover surveys, while administered interview was used to gather information on CPUE. The protection of fish sanctuary has shown its impact to the coral reef fisheries by the improvement in quantity of the resources. Fishes, macro-invertebrates, and hard coral cover inside the Sabang Reef Fish Sanctuary (Binduyan) showed increased in abundance, diversity, and number of commercial species compared to those outside of the sanctuary. This reflects the positive impact that a protected area gained over four years. Results indicated high exploitation rates of resources in the fished areas just outside the sanctuary. Furthermore, as a consequence of improved reef fisheries, more fishermen fishing in areas closest to the sanctuary have increased their catch.
Keywords: Coral reefs and islands -- Preservation and restoration; Fish conservation -- Honda Bay -- Puerto Princesa (Palawan)